THE EFFECT OF PRICE, PRODUCT QUALITY, SOCIAL MEDIA MARKETING AND BRAND IMAGE ON CONSUMER SATISFACTION MEDIATED BY BUYING INTEREST IN THE MS GLOW STORE LAMONGAN CENTER BY IID CENTER - Iddatul Fitriyah; Abid Muhtarom; Ruswaji Ruswaji; Mohammad Yaskun; Yunni Rosmawati DJ (Universitas Nusa Cendana, 2025)
This study aims to determine whether price, product quality, social media marketing, and brand image have a significant positive effect or not on consumer satisfaction mediated by buying interest. This type of research uses a quantitative approach, with a sample size of 177, and uses the SEM-PLS version 4 method. With the Outer Model Test, Inner Model Test, Mediation Test, and Hypothesis Test. The conclusion in the hypothesis test is that the variable price, product quality, social media marketing, and brand image on customer satisfaction are stated to have a positive and significant effect. Then in the Mediation Test, the variable price, product quality, social media marketing, and brand image on customer satisfaction mediated by buying interest is called partial mediation. Keywords: Price; Product Quality; Social Media Marketing; Brand Image